Workload Analysis Using the Full-Time Equivalent Method Based on the Business Process Management Approach at PT XYZ - Gima Yumima Alemisa Br Sinulingga; Satya Rizky Suhermanto; Annisa Rahmania; Sri Tjondro Winarno Suhermanto (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2026)
Effective human resource management is a key factor in ensuring the smooth operation of a company. Mismatches between the number of employees and the workload must be addressed to prevent low productivity or waste of resources. PT XYZ is a corn seed processing company. PT XYZ’s warehouse plays a crucial role in the entire process, from receiving to shipping out seed materials. This underscores the importance of measuring the workload within the warehouse. This workload measurement employs the Full-Time Equivalent (FTE) method through a Business Process Management (BPM) approach. Data was collected primarily through interviews, observations, and time measurements using a stopwatch, supplemented by secondary data in the form of warehouse Standard Operating Procedures (SOPs). Based on the analysis, the warehouse workflow at PT XYZ is divided into three categories: Work in Process (WIP), Production Material Chemical Material (PMCM), and finished goods. The calculated workload per employee in the warehouse is 1.034. This indicates that the workload level in the warehouse is considered normal.